New developments in the management of age-related macular degeneration - Lang, Gabriele E. (Zdravniški vestnik, 2004)
Background. Age-related macular degeneration (AMD) is one of the most important challenges that ophthalmologists are facing in this century. If unrecognized, AMD can lead to rapid vision loss having a severe impact on the daily life of affected patients by reducing functional abilities. AMD is the leading cause of blindness in elderly people in industrialized countries, a fact many people are not aware of. Conclusions. To date treatment options are only available in the late stages of AMD. In the neovascular form, thermal coagulation of choroidal neovascularization (CNV) is still the treatment of choice if the centre of the fovea is not involved. However, this treatment is suitable for only a small number of patients. Recently, photodynamic therapy (PDT) was introduced as a new treatment modality consisting of an intravenous infusion of a photosensitizing drug (verteporfin) which is then activated by alow-energy laser resulting in a specific occlusion of the CNV PDT has been shown to reduce the risk of vision loss in subfoveal predominantly classic andoccult CNV secondary to AMD. Early detection, exact diagnosis, and prompt treatment of AMD therefore play an important role in managing patients with AMD in the future.
Keywords: Choroid; degenerativne bolezni; Fluorescein Angiography; Fluorescenčna angiografija; Fotokemoterapija; Horoidea; Macular Degeneration; makula; Makula, degeneracija; Neovascularization, Pathologic; Neovaskularizacija patološka; očesne bolezni; Photochemotherapy; therapy; zdravljenje